1986
DOI: 10.1246/bcsj.59.661
|View full text |Cite
|
Sign up to set email alerts
|

Amijitrienol and 14-Deoxyisoamijiol, Two New Diterpenoids from the Brown Seaweed Dictyota linearis

Abstract: The structures of amijitrienol and 14-deoxyisoamijiol, two new diterpenoids isolated from the brown seaweed Dictyota linearis, have been established as 1 and 2 on the basis of spectral and chemical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…The dolastane diterpenes (1) and (2) are known compounds previously isolated from D. divaricata and D. linearis (Sun et al, 1981;Crew et al, 1982) and an unidentified Dictyota from the Canary Islands (Gonzalez et al, 1983). Several of these diterpenoids showed antimicrobial activity against Bacillus subtilis and Penicillium crustosum (Ochi et al, 1980), Staphylococcus aureus and Mucor mucedo (Ochi et al, 1986) and as cytotoxic compounds (Crew et al, 1982). Although some diterpenes have been isolated from Dictyota spp., it was shown that two of them are inhibitors of Na + K + -ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…The dolastane diterpenes (1) and (2) are known compounds previously isolated from D. divaricata and D. linearis (Sun et al, 1981;Crew et al, 1982) and an unidentified Dictyota from the Canary Islands (Gonzalez et al, 1983). Several of these diterpenoids showed antimicrobial activity against Bacillus subtilis and Penicillium crustosum (Ochi et al, 1980), Staphylococcus aureus and Mucor mucedo (Ochi et al, 1986) and as cytotoxic compounds (Crew et al, 1982). Although some diterpenes have been isolated from Dictyota spp., it was shown that two of them are inhibitors of Na + K + -ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…The dolastanes have been reported to show a wide range of biological activities, including cytotoxicity, histamine antagonism, antifungal, and antibiotic effects. [18][19][20][21] Interestingly, they are structural relatives of the potent antibiotic, guanacastepene A. [22] Several dolastanes, such as isoamijiol (4), dolastatrienol 6, and 14-deoxyisoamijiol, have been successfully synthesized as racemates and as the unnatural antipodes.…”
Section: Introductionmentioning
confidence: 99%
“…The dolastanes are tricyclic natural products isolated from the same algal species, and are characterized by the presence of an additional cyclopentane ring C fused to the AB rings of the secodolastanes. The dolastanes have been reported to show a wide range of biological activities, including cytotoxicity, histamine antagonism, antifungal, and antibiotic effects 1821. Interestingly, they are structural relatives of the potent antibiotic, guanacastepene A 22…”
Section: Introductionmentioning
confidence: 99%
“…Many of these diterpenes were isolated from other populations of this species and also from populations of C. crispatus (as Dictyota crispata) from Brazil [12]. In this context, the populations named Dictyota divaricata and D. linearis from the Caribbean Sea [13,14] and Japan [15][16][17][18], D. dichotoma [19][20][21][22] and D. indica from Pakistan [23][24], D. furcellata from Australia [25] and Dictyota sp. from the Canary Islands [26] could be considered as C. cervicornis.…”
mentioning
confidence: 99%